Respuesta :

Answer:

a^(b(c))

Step-by-step explanation:

(a^b)^c

a^(b(c))

Answer:

Add the powers.

Step-by-step explanation:

Let's say that we have:

[tex]3^2*3^3[/tex]

The "Product Rule" of exponents states that if you are multiplying powers that have the base, then you would have to add the powers.

[tex]a^n*a^m=a^{n+m}[/tex]

So, to solve the expression we have to apply the rule:

[tex]3^2*3^3\\\text{Apply Product Rule: } a^n*a^m=a^{n+m}\\\rightarrow 2+3=5\\\boxed{3^2*3^3=3^5}[/tex]

Hope this helps.